Transitioning care in cystic fibrosis: a comprehensive review of reviews of clinical and psychosocial outcomes - Alzayed, Abdullah (Frontiers in Pediatrics, 2025)
BackgroundWith rising life expectancy in cystic fibrosis (CF), effective transition from pediatric to adult care is essential. Structured transition models are thought to improve continuity of care, clinical stability, and psychosocial outcomes. This review of reviews synthesizes systematic review evidence on the effectiveness of these models across healthcare systems.MethodsReviews and systematic reviews with or without meta-analysis published between 2005 and 2025 were identified through comprehensive searches. Methodological quality was assessed using AMSTAR 2, and primary study overlap was quantified using the Corrected Covered Area (CCA). A narrative synthesis was conducted for all included reviews, stratified by intervention type and geography.ResultsStructured programs consistently outperformed informal approaches. Joint pediatric–adult clinics were associated with preserved lung function and fewer hospitalizations. The use of readiness tools, such as the Transition Readiness Assessment Questionnaire, showed improvement in self-management skills. Transition coordinators enhanced adherence and improved patient satisfaction with care. Evidence was limited regarding the long-term impact on mortality or transplant status.ConclusionStructured transition models, particularly those incorporating joint clinics and coordinator-led care, are effective in improving self-management, adherence, and continuity of care for adolescents and young adults with CF. Future systematic reviews should focus on synthesizing evidence for long-term clinical outcomes.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42025214760, PROSPERO CRD42025214760.